2022
DOI: 10.1002/uog.24974
|View full text |Cite
|
Sign up to set email alerts
|

Utility of trio‐based prenatal exome sequencing incorporating splice‐site and mitochondrial genome assessment in pregnancies with fetal ultrasound anomalies: prospective cohort study

Abstract: What are the novel findings of this work?Trio-based prenatal exome sequencing (pES) had an incremental yield of 31% in ongoing pregnancies with fetal ultrasound anomalies but undiagnosed by copy-number variant sequencing (CNV-seq). Comprehensive analysis of nuclear exome coding and splicing regions, as well as mitochondrial genome, provided not only diagnostic findings but also incidental findings (in 7.8% cases) that were important for affected families. What are the clinical implications of this work?Trio-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In 2021, Mellis et al published a systematic review of 72 studies on prenatal ES, 23 of which reported incidental findings with a 6.3% (129/2062) mean yield, with 5 studies yielding above 10% [ 12 ]. One of these groups, Zhu et al, reported 4 (4.4%) incidental findings among 90 pregnancies undergoing trio-based ES incorporating splice-site and mitochondrial genome analysis among fetuses with structural abnormalities [ 13 ] All findings had clinical relevance because the four couples chose to terminate their pregnancies [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Mellis et al published a systematic review of 72 studies on prenatal ES, 23 of which reported incidental findings with a 6.3% (129/2062) mean yield, with 5 studies yielding above 10% [ 12 ]. One of these groups, Zhu et al, reported 4 (4.4%) incidental findings among 90 pregnancies undergoing trio-based ES incorporating splice-site and mitochondrial genome analysis among fetuses with structural abnormalities [ 13 ] All findings had clinical relevance because the four couples chose to terminate their pregnancies [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…All fetal samples were tested for maternal cell contamination using a PowerPlex 21 HS System Kit (Promega Corporation, Madison, WI, USA). Exome capture and sequencing, read alignment, and bioinformatics analyses were performed as previously described [11].…”
Section: Dna Preparation and Trio-based Esmentioning
confidence: 99%
“…Small (one or two) exon deletions and single nucleotide variation in areas with poor coverage may also be missed. A potential remedy for this problem is whole-genome sequencing, but it is more expensive than whole-exome sequencing and results in a depth of sequence coverage that is lower than that achieved by whole-exome sequencing (Zhu et al 2022).…”
Section: Mitochondrial Genome Variantmentioning
confidence: 99%